La-Klems: Economic Growth and Productivity in Latin America - Aravena-Flores, C; Hofman, A (Cambridge University Press, 2016)
Introduction In the last two decades, the comparatively poor performance of economic growth in Latin America (LA) masks significant changes in both its sources and growth patterns. This chapter examines economic growth, productivity, and its determinants in five countries in Latin America for the period 1990-2010 for the aggregate economy as well as for nine economic sectors. In our analysis we use a new database, LA-KLEMS, which serves as a fundamental tool for research in the area of economic growth and productivity. The variables are organized around the growth accounting methodology, which provides a clear conceptual framework for analyzing interaction between variables in a consistent manner. LA-KLEMS is part of the World KLEMS initiative led by Professor Dale W. Jorgenson. An overview of this initiative can be found in Jorgenson (2016). The countries participating in LA-KLEMS are Argentina, Brazil, Chile, Colombia, and Mexico, and the project will continue to expand to include other countries in the region. Information provided on these countries is broken down into nine industries. Although the main objective of generating the KLEMS database is to identify comparative productivity trends, the data collected are also useful for a large number of other purposes because of the database’s comprehensive and detailed coverage. The data series follow the format of EU-KLEMS (see Timmer, Inklaar, O’Mahony and van Ark 2010) including measures of production and growth factors and variables in various categories of capital (K), labor (L), energy (E), materials (M), and service inputs (S). The LA-KLEMS database is largely built upon the information provided by the national statistical institutes (INE) and/or central banks, and is processed according to internationally standardized procedures. These procedures have been developed to ensure international comparability of data and generate coherent series. The KLEMS data are based both on national accounts statistics for each country and on the concepts and conventions of the System of National Accounts. Employment statistics, labor information coming from household and/or employment surveys, and, in some cases, social security registers, are also used to obtain the most consistent series for hours worked. This brand new database is particularly relevant for Latin America countries, as comparable studies on economic growth and productivity have been hampered by the lack of standard databases covering a wide range of countries. The KLEMS methodology allows for comparable cross-country series of the main variables associated with economic growth and productivity. © Cambridge University Press 2016.